2014
DOI: 10.1002/bies.201300147
|View full text |Cite
|
Sign up to set email alerts
|

Molecular network analysis enhances understanding of the biology of mental disorders

Abstract: Summary We provide an introduction to network theory, evidence to support a connection between molecular network structure and neuropsychiatric disease, and examples of how network approaches can expand our knowledge of the molecular bases of these diseases. Without systematic methods to derive their biological meanings and inter-relatedness, the many molecular changes associated with neuropsychiatric disease, including genetic variants, gene expression changes and protein differences, present an impenetrably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 121 publications
(162 reference statements)
0
12
0
Order By: Relevance
“…The co-expression profiles shown in Figures 2 and 3 are particularly intriguing as co-regulation networks in recent years have been closely related to tissue-and cell type-specific biological functions and disturbances (Kopp et al, 2015; Monaco et al, 2015; Richiardi et al, 2015; Rotival and Petretto, 2014). Co-expression patterns in the brain are particularly of interest given the developmental concept of complex neuropsychiatric disorders, where it has been historically difficult to identify single causal molecular relationships (Gaiteri et al, 2014; Grennan et al, 2014). While the exact nature of the correlations between different genes and how germline THC exposure affects these relationships in subsequent progeny remains to be explored, our observations emphasize the importance of studying functional networks of genes in relation to cannabis exposure in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The co-expression profiles shown in Figures 2 and 3 are particularly intriguing as co-regulation networks in recent years have been closely related to tissue-and cell type-specific biological functions and disturbances (Kopp et al, 2015; Monaco et al, 2015; Richiardi et al, 2015; Rotival and Petretto, 2014). Co-expression patterns in the brain are particularly of interest given the developmental concept of complex neuropsychiatric disorders, where it has been historically difficult to identify single causal molecular relationships (Gaiteri et al, 2014; Grennan et al, 2014). While the exact nature of the correlations between different genes and how germline THC exposure affects these relationships in subsequent progeny remains to be explored, our observations emphasize the importance of studying functional networks of genes in relation to cannabis exposure in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Of special interest, from a systems biology perspective, we found several topographic parameters of protein-protein interaction networks that were significant for NPD genes [30, 31]. We found that 66 NPD genes are known to be druggable, a finding of relevance for development of novel therapeutic interventions [19].…”
Section: Discussionmentioning
confidence: 99%
“…The field has moved past looking for simple Mendelian factors, and towards identifying functional aspects of the molecular changes underlying challenging complex disorders. Today, pathway analysis, network analysis [15,16] and in silico prediction of functional variation produced by coding variants are common practice. Functional analysis of non-coding variants is a major challenge facing the field [17].…”
Section: Remember That Proof Of Biological Function Is Needed To Sumentioning
confidence: 99%